The impact of philosophical and theoretical/epistemological productions on the constitution of the discipline - González-Saibene Alicia (Critical Proposals in Social Work, 2021)
This article aims to work on the relationship between philosophy and epistemology with social work, assuming a genealogical reading of its evolution that will allow us to highlight the points of contact and the divergences. A critical analysis of the current positions on Mary Richmond’s productions is presented, reflecting on her influences, her contributions and her positions, asking ourselves what is the connection between these interpretative views and the more positivist / functionalist epistemic positions of the social work, or even those oriented towards Marxism / dialectics, insofar as these two approaches have been, in different periods, hegemonic in the profession / discipline? To elaborate on this discussion, we refer to another disciplinary field: Ferdinand de Saussure’s contributions to structural linguistics, alongside psychoanalysis. These perspectives allow us to consider language as an ordering principle and to show the emergence and relevance of the interpretive approach. We propose this reading precisely because we consider the difficulty social work has had to be included in this perspective, despite the ingrained technical-instrumental and theoretical-epistemic traditions that advocate or promote the importance of interpretation. The end of the text opens up new questions, rather than formally elaborated answers. The opening and closing point, in a spiral, is reflexivity and criticism.